Case report: Palliation of right pulmonary artery compression with overlapping, self-expanding vascular stents and toceranib phosphate in a dog with a large, compressive chemodectoma - Ferrel, Claudia Serrano; Winter, Randolph L.; Maneval, Kara L.; Matz, Brad M.; Bergman, Noelle S.; Starbird, Cierra; Koehler, Jey; Liao, PenTing (Frontiers in Veterinary Science, 2024)
Acquired pulmonary artery branch stenosis without main pulmonary artery involvement due to external compression by neoplasia has been described in human and veterinary medicine. Over time, this can result in right ventricular hypertension and right-sided heart failure. Endovascular stenting offers quick relief from signs, while the underlying cause is addressed. Here, we present a dog with severe right pulmonary artery compression caused by a chemodectoma, which was treated with two, overlapping, self-expanding vascular stents and chemotherapy. The patient experienced immediate symptomatic relief, progressive stent expansion over time, and has been free of clinical symptoms for 5 months post implantation.